Microbiologically influenced corrosion of FeCoNiCrMn high-entropy alloys by Pseudomonas aeruginosa biofilm - Yang, Jike; Zhang, Yu; Chang, Weiwei; Lou, Yuntian; Qian, Hongchang (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is widely found in industrial water and seawater. Microbiologically influenced corrosion (MIC) caused by P. aeruginosa is a serious threat and damage to the safe service of steel materials. In this study, the MIC behavior of FeCoNiCrMn high-entropy alloy (HEA) by P. aeruginosa biofilm was investigated in the simulated marine medium. The maximum pitting depth of the HEA coupons in the P. aeruginosa-inoculated medium was 4.77 μm, which was 1.5 times that in the sterile medium. EIS and potentiodynamic polarization results indicated that P. aeruginosa biofilm reduced the corrosion resistance of the passive film of HEA coupons and promoted its anodic dissolution process. XPS and AES results further demonstrated that P. aeruginosa interfered with the distribution of elements in the passive film and significantly promoted the dissolution of Fe.